2008
DOI: 10.1590/s0004-27302008000400019
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol injection under ultrasound guidance to palliate unresectable parathyroid carcinoma

Abstract: Background: Severe hypercalcemia is the leading cause of death in patients with parathyroid carcinoma. Non-curative resection and pharmacological measures may be useful for palliation in cases with recurrent and metastatic disease. Palliative treatment with intra-neoplastic ethanol injection has not been reported yet. Methods: Ultrasound-guided percutaneous alcohol injection in one patient with unresectable parathyroid carcinoma is reported. Results: One male patient with extensive recurrent parathyroid carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…6,9,12 In 1 study 6 comparing complication rates of surgical parathyroidectomy, heat ablation, and ethanol ablation in dogs, no significant difference among complication rates was found. 14 The purpose of the study reported here was to describe outcomes for dogs with primary hyperparathyroidism following treatment with percutaneous ultrasound-guided ethanol ablation of presumed functional parathyroid nodules. 6,9 Humans undergoing ethanol ablation procedures describe a transient, tolerable pain at the injection site.…”
mentioning
confidence: 99%
“…6,9,12 In 1 study 6 comparing complication rates of surgical parathyroidectomy, heat ablation, and ethanol ablation in dogs, no significant difference among complication rates was found. 14 The purpose of the study reported here was to describe outcomes for dogs with primary hyperparathyroidism following treatment with percutaneous ultrasound-guided ethanol ablation of presumed functional parathyroid nodules. 6,9 Humans undergoing ethanol ablation procedures describe a transient, tolerable pain at the injection site.…”
mentioning
confidence: 99%
“…При невозможности хирургического лечения могут применяться методы локального воздействия, в том числе радиочастотная абляция метастатических очагов в легких и печени, а также трансартериальная эмболизация [11][12][13]. Сообщалось об успешной склеротерапии местных рецидивов 96 % этанолом [25], однако высокая частота повреждения этанолом возвратного гортанного нерва не позволяет широко использовать данную Опухоли ГОЛОВЫ и ШЕИ HEAD and NECK tumors Том 10 Vol. 10 3'2020 Диагностика и лечение опухолей головы и шеи методику при очагах на шее [26].…”
Section: Note Hte -Hemithyroidectomy; Lnd -Lymph Node Dissection; Ptunclassified
“…Given the development of jaw tumors, a dental panorex image every 5 years is also recommended [49]. In patients with diagnosed PC, lifelong surveillance is recommended [50,51].…”
Section: Surveillance/follow-upmentioning
confidence: 99%
“…True efficacy of this treatment remains unknown, however, as only anecdotal case reports exist. Likewise, isolated reports of ethanol ablation temporarily decreasing serum calcium and PTH levels suggest use of ultrasound-guided injection for palliation of PC in selected cases [50]. This modality, however, should be reserved for disease outside of the central neck, as ethanol injection in the central neck can permanently injure a functioning recurrent laryngeal nerve.…”
Section: New Developments/future Treatmentmentioning
confidence: 99%